Fairer Election - The Star, Karan Chapman (2008)
Some 100 students from Solidariti Mahasiswa Malaysia (SMM) held a demonstration at Universiti Kebangsaan Malaysia (UKM) in Bangi last Friday demanding fair campus elections.